2017
DOI: 10.1088/1361-6455/aa8b3b
|View full text |Cite
|
Sign up to set email alerts
|

Bound and resonance states of positronic copper atoms

Abstract: We report a theoretical calculation for the bound and S-wave resonance states of the positronic copper atom (e + Cu). A positron is a positively charged particle; therefore, a positronic atom has an attractive correlation between the positron and electron. A Gaussian expansion method is adopted to directly describe this correlation as well as the strong repulsive interaction with the nucleus. The correlation between the positron and electron is much more important than that between electrons in an analogous sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In the present calculation, we consider a Schrödinger equation (H − E ν )Ψ ν = 0 where the fourbody Hamiltonian H contains kinetic energy operators (separated from the center-of-mass motion) and all inter-particle Coulomb potential energy operators. We adopt a Gaussian expansion method (see reviews [17][18][19] and our recent calculations [20][21][22][23][24]) for the four-body wave function Ψ ν . The Ψ ν is expanded in terms of Gaussian basis functions ϕ il (r) = N il r l exp(−r 2 ) (N il is a normalization constant) and spherical harmonics as follows:…”
Section: Theorymentioning
confidence: 99%
“…In the present calculation, we consider a Schrödinger equation (H − E ν )Ψ ν = 0 where the fourbody Hamiltonian H contains kinetic energy operators (separated from the center-of-mass motion) and all inter-particle Coulomb potential energy operators. We adopt a Gaussian expansion method (see reviews [17][18][19] and our recent calculations [20][21][22][23][24]) for the four-body wave function Ψ ν . The Ψ ν is expanded in terms of Gaussian basis functions ϕ il (r) = N il r l exp(−r 2 ) (N il is a normalization constant) and spherical harmonics as follows:…”
Section: Theorymentioning
confidence: 99%
“…The total Hamiltonian for pH is written as In order to describe the all inter-particle correlation of the near-threshold resonance states precisely, we adopt a Gaussian expansion method (GEM) [34]. Recently the GEM approach successfully revealed the near-threshold resonances in positronic atom systems [35][36][37]. Besides, this approach can be applied to the four-body system HH in the same theoretical framework [33,38].…”
Section: Theorymentioning
confidence: 99%
“…It has been pointed out that the positron cannot form a bound state with a neutral hydrogen atom and helium atom; therefore, the simplest positronic atom is a positronic lithium atom (e + Li) whose electronically stable bound state was theoretically proved by a precise calculation in 1997 [5,6]. Theoretical investigations performed since then have revealed that positronium (Ps, a bound state of e + and e − ) formation by configuration rearrangement can contribute to the binding mechanism of the positronic atoms [7][8][9][10][11]. A host atom like lithium, whose ionization energy is smaller than the binding energy of positronium, can capture the Ps by the electric field of the residual ion.…”
Section: Introductionmentioning
confidence: 99%